Characterization of Klebsiella spp from healthy swine: virulence, resistance to antimicrobials and gene transferer mediated by extracellular vesicles - Rosa, Jéssica Nogueira (2023)
Bacteria of the Klebsiella genus belong to the Enterobacteriaceae family, are Gram-negative and exhibit different habitats and ecological functions, especially in other hosts. The most studied species is Klebsiella pneumoniae, a bacteria naturally found in the intestinal microbiota and na important opportunistic pathogen. The virulence factors attributed to K. pneumoniae are the production and secretion of siderophores, type I and III fimbriae, polysaccharide capsules, lipopolysaccharides (LPS), secretion system (T6SS) and extracellular vesicles (EVs). Factors involved with virulence and antimicrobial resistance are variable and encoded by different genes. Theses genes can be acquired by horizontal transfer (THG) with the effective participation of mobile genetic elements (MGE), such as plasmids and conjugative integrative elements (ICE). Swine have Klebsiella spp as members of the intestinal microbiota and may be reservoirs of this genus with genetic markers of virulence and resistance. Therefore, this work had the following objectives: to isolate Klebsiella spp from healthy swine in growth phase II; characterize the phenotype and genotype of virulence and antimicrobial resistance; to investigate the contribution of ICEs to their ecological niche as well as horizontal gene transfer mediated by extracellular vesicles (EVs). As a result of chapter 1, 144 Klebsiella spp isolates were obtained, of which 77% were identified as K. pneumoniae, 14.5% Klebsiella aerogenes, and 8.5% Klebsiella variicola. In the isolates obtained, the following resistance profile was observed: β-lactams (100 %), cephalosporins (75.5 %), fluoroquinolones (51 %), phenicol (48.8 %), tetracycline (55.5 %), macrolide (37.7%), sulfonamide (35.5%), aminoglycoside (8.8%), trimethoprim (4.5%). Overall, 88.8% of the isolates were characterized as multidrug-resistant (MDR). Important virulence phenotypes and genotypes were identified as siderophore production (entB, iucB, iutA, kfu and ybtS/irp2) and biofilm, where 39% are classified as strong producers, 45% moderate and 16% as weak producers. The hypermucoviscous phenotype was not verified in the investigated isolates, however the iutA marker gene was identified in 19 isolates (42.2%). From the presented results, 11 isolates of K. pneumoniae MDR were selected for investigation of the type of sequence (STs) and they were classified as ST25, ST147, ST616, ST691 and ST6208. Thus, two isolates were selected for genome sequencing (chapter 2), K. pneumoniae HS-144 and K. pneumoniae HS-13. Functional annotation revealed classes such as metabolism of carbohydrates, amino acids, and proteins (37.6%); membrane transport (5.7%); cell regulation and signaling (3.5%); DNA metabolism (3.5%); virulence, disease and defense (3.1%); cell wall and capsule (5.2%) and others. Klebsiella pneumoniae HS-144 and K. pneumoniae HS-13 carry plasmids. Of the two strains, only genes involved in the complete conjugation apparatus (T4SS, T4CP, relaxase and oriT) and a phage carrying the blaSHV2 gene were identified in the HS-144 strain. For this strain (HS-144) the ESBL - extended-spectrum β- lactamase phenotype was also confirmed. Thus, a biparental conjugation assay using K. pneumoniae HS-144 as a donor and E. coli J53 as recipient (selection with colistin). Three transconjugants were obtained (MIC for colistin >64mg.mL-1), confirming the mobilizable nature of genetic determinants involved with resistance to colistin, a drug as a last resort in the treatment of K. pneumoniae in the human clinic. In chapter 3, 949 complete genomes of K. pneumoniae were investigated in order to characterize integrative and conjugative elements in the species. Of all the analyzed genomes, 501 genomes presented one or more potential regions with self-transfer capability, and 18.2% of these present co-occurrences with other ICEs. We detected 19 new ICE candidates. The new ICEs carry genes related to iron adhesion and absorption, capsule biosynthesis, cell wall and LPS, stress response, membrane components and resistance to arsenic, β-lactam, polymyxin and novobiocin. In addition, we also mapped four new ICEs that carry the highly pathogenic Island Yersinia (HPI). In Chapter 4, we investigated the importance of extracellular vesicles (EVs) in gene transfer between human and swine Klebsiella spp. EVs-Kp13 (K. pneumoniae Kp13) were obtained by the hydrostatic filtration method. The EVs obtained had an average size of 182 nm and rounded morphology. In this work, it was confirmed that EVs-Kp13 carry genes for resistance to sulfonamide (sul2), cephalosporins (blaCTXM2, blaSHV, blaTEM), carbapenems (blaKPC) and trimethoprim (dfrA15). Furthermore, it was detected that EVs-Kp13 carry genes that code for the siderophore yersiniabactin. Our blistering results were positive when using the K. aerogenes 270 strain as recipient, isolated from healthy swine. Four transvesiculants were obtained that showed resistance to cephalosporins (third and fourth generation) and trimethoprim, in addition to the marker genes of plasmid pKP13f. We can conclude that clinically healthy swine have Klesiella spp with a clinically relevant MDR and virulence phenotype in their normal microbiota. Klebsiella pneumoniae can also carry mobile genetic elements such as plasmids and ICEs that help their fitness in different environments. And finally, vesiduction can be an important means of disseminating resistance genes in Klebsiella spp. This study elucidates important gene flow routes between different species and reservoirs, significantly contributing to the unified health approach. Keywords: One health. Multidrug resistant. Microbial fitness. Vesiduction.